Age-period-cohort analysis of cervical cancer incidence in Hong Kong from 1972 to 2001 using maximum likelihood and Bayesian methods. Issue 8 (13th July 2006) - Leung, Gabriel M; Woo, Pauline P S; McGhee, Sarah M; Cheung, Annie N Y; Fan, Susan; Mang, Oscar; Thach, Thuan Q; Ngan, Hextan Y S
Abstract : Objective: To examine the secular effects of opportunistic screening for cervical cancer in a rich, developed community where most other such populations have long adopted organised screening. Design, setting, and participants: The analysis was based on 15 140 cases of invasive cervical cancer from 1972 to 2001. The effects of chronological age, time period, and birth cohort were decomposed using both maximum likelihood and Bayesian methods. Results: The overall age adjusted incidence decreased from 24.9 in 1972–74 to 9.5 per 100, 000 in 1999–2001, in a log-linear fashion, yielding an average annual reduction of 4.0% (p<0.001) during the 30 year period. There were two second order and thus identifiable changes: (1) around the mid-1920s cohort curve representing an age-period interaction masquerading as a cohort change that denotes the first availability of Pap testing during the 1960s concentrated among women in their 40s; (2) a hook around the calendar years 1982–83 when cervical cytology became a standard screening test for pregnant women. Conclusions: Hong Kong's cervical cancer rates have declined since Pap tests first became available in the 1960s, most probably because of increasing population coverage over time and in successive generations in a haphazard fashion and punctuated by the systematic introduction of routine cytology as part of antenatal care in the 1980s.